EDUCAŢIA PENTRU CETĂŢENIE ÎN ŞCOLILE DIN ROMÂNIA. UNELE ASPECTE ALE CURRICULUMULUI FORMAL, NONFORMAL ŞI INFORMAL - USM ADMIN (Moldova State University, 2007)
Education for responsible citizenship is crucial for the development of pluralist democracies in Romania. The Coun- cil of Europe is undertaking special programs to help countries in democratic transition to develop new curricula and teaching resources in these key subjects. This article shows that secondary schools should prepare young people for study, training, work, mobility, leisure and everyday living in a democratic and multicultural Europe.